Québec : Etudes sur la Geographie du Canada - Grenier, Fernand, 1927- (Études sur la géographie du Canada. Studies in Canadian geography ;, 1972)
This volume looks at the evolution and present patterns of the ecumene of southern Québec, rural and urban Québec, and the dynamic biogeography of Québec.